Community Service to Tandes Village Residents in the Form of Making Logo and Packaging Designs for Fermented Glutinous Rice Products - W, Owen Jonathan; Reinhart, Nicholas; D, Geraldwyne; Hugo, Carissa (Lembaga Yasin AlSys, 2024)
Small Medium Emeetrise (MSME) is a productive businessowned by individuals or business entities that meets the criteria for being a micro enterprise. MSME, because it is still a microbusiness, has many obstacles to develop. During COVID-19pandemic, many MSMEs in Tandes Village were forced to closetheir business. The level of demand also decreased significantly and thus led them near to bankruptcy. Through this program, we, Ciputra University students, are trying to contribute tosolutions to problems in society. This program aims to helpTandes village Fermented Glutinous Rice Products to be moreattractive and viable in various ways, that supports culinary tourism in Tandes village including marketing, trust, health and safety guarantees, and various other small product details. A visit to Tandes Village to provide support to MSMEs wascarried out on December 13, 2023. We all went there to handover the logo and packaging design. We also help promote theirproducts through our social media. From the results of ourpromotion, more than 20 product sales have been successfullycarried out and purchased by our relatives and friends.